“ESPAÇO E MORTE NAS REPRESENTAÇÕES SOCIAIS DAS TRAVESTIS E TRANSEXUAIS FEMININAS” - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
The research comprises as the spaces of death are represented by travestis and female transsexuals who actually lives in the State of Paraná. Space is part of heteronormativity. In turn, it is the general idea that structures the alleged linearity between sex, gender, desire e practice sexual. People like transvestites and transsexuals female transgress the rules established socially and suffer a range of sanctions that make it difficult their existence. This group is the most vulnerable to violence and death of LGBT people. Vulnerability to death also establishes how travestisand transsexuals female are their social representations of the city, especially those they recognize as spaces of death. Social representations are understood as common sense speeches establishing a set of significations around the space, bringing this paper to the concept of space as a text to be read and interpreted by specific social groups. In the case of this research, travestis and transsexuals who have female vulnerability to violence and death. For the construction of this dissertation we performed eight in-depth interviews with transvestites and female transsexuals who at that time resided in the state of Paraná. The stimulation of discourse about space and death was accomplished through the use of news on this topic, conveyed in newspapers online. The interviews were analyzed using content analysis which enabled founders recognize the meanings of social representations created by travestisand transsexuals on the relationship between space and death. Social representations imposed by the group bring the idea of increasing violence, blaming the group for their own condition of marginality and also brings the territory of prostitution as a possibility for life and simultaneously the risk of death.
Keywords: espaço; morte; representações sociais; travestis; transexuais femininas; space; death; social representations; travestis; tansgender female; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA